2012
DOI: 10.2174/138161212803307545
|View full text |Cite
|
Sign up to set email alerts
|

Mucoadhesive Polymers for Oral Transmucosal Drug Delivery: A Review

Abstract: Abstract:The oral mucosa offers an interesting site for the application of dosage forms that release drugs within/throughout the oral mucosa, by assuring a high drug bioavailability for topic and systemic effects. However, the relative permeability of the oral mucosa and the washing effect related to the oral fluids and mechanical stresses must be considered in the formulation of oral dosage forms. Since a sustained drug release can be guaranteed only if dosage forms remain in contact with the oral site of abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 136 publications
(226 reference statements)
0
28
0
9
Order By: Relevance
“…Although the marked increase in surface area during swelling can promote drug release, the increase in diffusion path length of the drug may paradoxically delay the release. In addition, the thick gel layer formed on the swollen film surface is capable of preventing matrix disintegration and controlling additional water penetration [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the marked increase in surface area during swelling can promote drug release, the increase in diffusion path length of the drug may paradoxically delay the release. In addition, the thick gel layer formed on the swollen film surface is capable of preventing matrix disintegration and controlling additional water penetration [15].…”
Section: Discussionmentioning
confidence: 99%
“…The buccal mucosa is one of the most suitable sites for MDDS [2,[4][5][6][7][8]. Attempts have been made to formulate various mucoadhesive devices including tablets, films, patches, disks, strips, ointments and gels [9][10][11][12][13][14][15][16]. Buccal film may be preferred over adhesive tablet in terms of flexibility and comfort.…”
Section: Introductionmentioning
confidence: 99%
“…These interactions are thought to be a result of the hydrogen bonds between g-PGA and the proton-accepting groups within the mucus glycoprotein. It was concluded that the mucoadhesive polymer could interact with the mucin molecule by physical chain entanglements followed by hydrogen bond formation with the sugar residues on the oligosaccharide chains, forming a strengthened gel network, thus allowing the polymer to remain adhesive for extended periods of time (38,39). As the polymer would be in an expanded uncoiled state at the pH of the medium (6.2) due to the electrostatic repulsion arising from the ionized functional groups, the polymer would be more susceptible to mechanical chain entanglement and secondary interactions with the mucus glycoprotein.…”
Section: Discussionmentioning
confidence: 99%
“…These experimental results suggest that g-PGA increased the residence time of the codelivered OVA Ags in the mucus layer and acted as a controlled-release reservoir for the nasal epithelial cells. We speculated that g-PGA could interact with mucin molecules through physical chain entanglements and form hydrogen bonds with the sugar residues on the oligosaccharide chains (38,39). Because g-PGA is in the expanded uncoiled state at the pH of the nasal secretions (pH 6.0-6.5), the electrostatic repulsion arising from the ionized functional groups renders g-PGA more susceptible to mechanical chain entanglement and secondary interactions with the mucous glycoprotein (40).…”
mentioning
confidence: 99%
“…Mucoadhesive polymers are used for the formulation of TMDDS. These polymers generally are the polymers and their different grades with high molecular weight, high viscosity, greater flexibility and optimum chain length [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%